Application of Biology to Cultural Heritage - Macedo, Maria Filomena; Portugal, António Manuel Santos Carriço; Miller, Ana; Pinheiro, Ana Catarina (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book compiles the Special Issue of Applied Sciences, entitled "Application of Biology to Cultural Heritage", and aims to cover all the latest outstanding progress on the biological and biochemical methods developed and applied to cultural heritage.Eleven excellent papers (including both reviews and full research articles) form part of this book and each paper went through a hard and demanding review in order to ensure maximum quality. We do thank all the reviewers for their efforts which are so crucial for the improvement of the now-published papers. In the field of cultural heritage, biodiversity and biodeterioration have received a great deal of research attention in recent years. This book intends to provide a comprehensive examination of the science of biology in various fields and areas, as well as its practical application for the preservation of cultural heritage. Full research articles and reviews on all aspects of biological causes, modes of action, biocidal treatments, and the protection of cultural heritage are here presented, as well as long-term studies on the biodeterioration of cultural heritage sites and monuments.Analyses and tests of macro- and micro-organisms affecting the preservation of cultural heritage are also addressed.The knowledge that has arisen from the papers published on the studies on new techniques and new products applied to the field of cultural heritage may now be translated into new conservation and restoration treatments in similar objects, sites and supports. This was the main goal and it was achieved in a mission that we carried out with great pleasure and dedication.